Graphite negative electrode active material, preparation method thereof, secondary battery containing graphite negative electrode active material, and electric device containing graphite negative electrode active material

By controlling the particle size and morphology of graphite negative electrode active material and optimizing the structure of the negative electrode film layer, the problems of local polarization and side reactions of secondary batteries during the cycle are solved, and a longer cycle life and more stable storage performance are achieved.

CN119852401APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311679774.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the cycle process, existing secondary batteries have local polarization, uneven current distribution and reduced capacity retention rate caused by side reactions, which affects the long cycle life of the battery.

Method used

By controlling the volume distribution particle size Dv1 of graphite negative electrode active material within the range of 1.5 μm-3 μm, and ensuring that the material is mainly based on the primary particle morphology, combining the appropriate specific surface area and tap density, the compaction density and surface density of the negative electrode film layer are optimized to improve the cycling performance of the battery.

Benefits of technology

It effectively improves the cycling performance of the battery, extends the service life of the battery, and reduces the impact of side reactions and lithium-ion phenomena on battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852401A_ABST
    Figure CN119852401A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode active material, a preparation method thereof, a secondary battery containing the graphite negative electrode active material and an electric device. The volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5-3 [mu] m, and the graphite negative electrode active material comprises a primary particle morphology. The graphite negative electrode active material can improve the cycle performance of the battery and prolong the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a graphite negative electrode active material and a preparation method thereof, a secondary battery containing the same, and an electrical device. Background Art

[0002] With the introduction of carbon neutrality goals and policies, the secondary battery market for energy storage has ushered in a huge explosion. For energy storage batteries, long cycle life is a key indicator, especially for energy storage batteries used in large-scale energy storage power stations. In order to extend service life and reduce replacement frequency, it is necessary to further develop energy storage batteries with longer cycle life. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a graphite negative electrode active material and a preparation method thereof, a secondary battery and an electrical device containing the same, which can effectively improve the cycle life of the battery and extend the service life of the battery.

[0004] A first aspect of the present application provides a graphite negative electrode active material, wherein the volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5 μm-3 μm; the graphite negative electrode active material includes a primary particle morphology.

[0005] The volume distribution particle size Dv1 of the graphite negative electrode active material is within a suitable range, and the material has a specific particle morphology, which can make the negative electrode plate have an excellent liquid absorption rate. During the battery cycle, the electrolyte can fully infiltrate the negative electrode plate during the repeated lithium insertion and extraction process of the negative electrode, reducing the possibility of local polarization, making the current of the negative electrode plate uniformly distributed during the cycle, reducing the possibility of side reactions at the negative electrode interface during the cycle, and reducing the effect of the byproducts caused by the side reactions blocking the pores on the battery cycle performance. At the same time, the volume distribution particle size Dv1 in a suitable range is conducive to improving the binding force between the particles of the graphite negative electrode active material, effectively maintaining the electrical contact between the particles, improving the kinetic performance of the battery, and reducing the negative impact of lithium precipitation on the cycle performance.

[0006] On the other hand, the graphite negative electrode active material includes primary particles, which have excellent structural stability, which helps to reduce the structural fragmentation of the graphite negative electrode active material caused by expansion and contraction during the cycle process, improve the structural stability of the graphite negative electrode active material, and thus improve the cycle performance of the secondary battery.

[0007] In summary, the present application can effectively improve the cycle performance of the battery and extend the service life of the battery by limiting the volume distribution particle size Dv1 of the graphite negative electrode active material and the particle type of the graphite negative electrode active material.

[0008] In any embodiment, the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, optional 0.6m 2 / g-1.3m 2 / g.

[0009] The specific surface area of ​​the graphite negative electrode active material satisfying the above range is helpful to reduce the side reactions of the graphite negative electrode active material during the cycle process, reduce the loss of active lithium, and is beneficial to improving the storage stability and cycle stability of the battery.

[0010] In any embodiment, the volume distribution particle size Dv50 of the graphite negative electrode active material is 12 μm-16 μm, and can be optionally 13 μm-15 μm.

[0011] The graphite negative electrode active material has a large volume distribution particle size Dv50, which is conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, which is conducive to the full infiltration of the electrolyte into the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of black spots on the negative electrode on the cycle life and storage stability of the battery.

[0012] In any embodiment, based on the total number of particles of the graphite negative electrode active material, the number of the primary particles accounts for greater than or equal to 80%, and can be optionally 85%-100%.

[0013] The primary particles within the above range help to reduce the structural breakage of the graphite negative electrode active material caused by expansion and contraction during the cycle process, improve the structural stability of the graphite negative electrode active material, and further improve the cycle performance and storage life of the secondary battery.

[0014] In any embodiment, the gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g, and can be optionally 341 mAh / g-347 mAh / g.

[0015] Graphite negative electrode active materials have high gram capacity, providing a material basis for high energy density batteries. At the same time, the gram capacity of graphite negative electrode active materials is within the above range, and its particle strength is high, which reduces the possibility of particles tending to be flat during the cold pressing of the pole piece, avoids the transmission path of the electrolyte from becoming significantly longer during the cold pressing process, is conducive to reducing the tortuosity of the negative electrode piece, is conducive to the circulation of the electrolyte, and improves the cycle performance and storage stability of the battery.

[0016] In any embodiment, the tap density of the graphite negative electrode active material is 1.2 g / cm 2 -1.4g / cm 2 .

[0017] When the tap density of the graphite negative electrode active material is within the above range, it is conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, improving the wettability of the electrolyte to the negative electrode plate, and improving the cycle performance and storage stability of the secondary battery. At the same time, the appropriate tap density can also increase the compaction density of the negative electrode film layer, thereby improving the energy density of the secondary battery.

[0018] In any embodiment, the particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.20-1.70, and can be 1.35-1.60.

[0019] The particle size distribution of the graphite negative electrode active material that meets the above range is helpful to improve the concentration of the particle size of the graphite negative electrode active material, improve the concentration of the particle arrangement, reduce the tortuosity of the negative electrode plate, allow the electrolyte to fully infiltrate the negative electrode plate, and improve the cycle performance of the battery. At the same time, it can also reduce the uneven distribution of active ions in the graphite negative electrode active material caused by the large difference in particle size, reduce the side reactions of the graphite negative electrode active material with smaller particle size and the electrolyte, and improve the cycle performance and storage stability of the secondary battery. At the same time, the particle size distribution of the graphite negative electrode active material is within the above range, and its particle stacking performance is good, which is conducive to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0020] The second aspect of the present application provides a method for preparing a graphite negative electrode active material, comprising the following steps: providing raw materials; processing the raw materials to obtain a precursor; graphitizing the precursor to obtain an intermediate product; screening the intermediate product to obtain a graphite negative electrode active material; wherein the volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5μm-3μm; and the graphite negative electrode active material includes a primary particle morphology.

[0021] By adopting the above preparation method, a graphite negative electrode active material with a volume distribution particle size Dv1 within a suitable range and a primary particle morphology as the main component can be prepared, which can further improve the cycle performance of the battery and extend the service life of the battery.

[0022] In any embodiment, the processing of raw materials specifically comprises the following steps:

[0023] crushing, shaping and classifying the raw materials to obtain a precursor;

[0024] During the classification process, a certain proportion of fine powder is removed.

[0025] Among them, the mass proportion of the removed fine powder is 10%-35%. Based on the total mass of the raw material, the volume distribution particle size Dv50 of the fine powder is 3μm-7μm, and the (Dv90-Dv10) / Dv50 of the fine powder is greater than 1.6.

[0026] By controlling the mass proportion of fine powder within an appropriate range, the volume distribution particle size Dv1 of the graphite negative electrode active material can be controlled within an appropriate range, which can not only make the electrode have an excellent liquid absorption rate and the electrolyte can fully infiltrate the negative electrode, but also make the graphite particles have excellent electrical contact, thereby comprehensively improving the cycle performance of the battery.

[0027] In any embodiment, the power used in the graphitization process is 70%-90% of the rated power of the graphitization equipment.

[0028] In any embodiment, the power used in the graphitization treatment is 23000W-25000W.

[0029] In any embodiment, the holding time of the graphitization treatment is 10h-50h.

[0030] In any embodiment, the precursor satisfies at least one of the following conditions:

[0031] The volume distribution particle size Dv50 of the precursor is 12 μm-18 μm; and / or,

[0032] The particle size distribution of the precursor (Dv90-Dv10) / Dv50 is 1.2-1.8.

[0033] A third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the graphite negative electrode active material of the first aspect or the graphite negative electrode active material prepared by the preparation method of the second aspect.

[0034] In any embodiment, the compaction density of the negative electrode film layer is 1.35 g / cm 3 -1.65g / cm 3 , optional 1.40g / cm 3 -1.55g / cm 3 .

[0035] The smaller the compaction density of the negative electrode film, the more pores in the negative electrode film and the larger the pore size, the easier it is for the electrolyte to enter the negative electrode pores, and the easier it is for the electrolyte to infiltrate the negative electrode sheet. However, if the compaction density of the negative electrode film is too small, the energy density of the battery will decrease, and it will also affect the bonding between the active material and the current collector in the negative electrode film, as well as the bonding between the active materials, resulting in the shedding of active materials during the cycle, and even causing safety accidents.

[0036] The compaction density of the negative electrode film layer falls within the above range, which can ensure that the negative electrode film layer has abundant pores, and the electrolyte can easily infiltrate the negative electrode plate, thereby improving the cycle performance and storage stability of the battery, and the battery has a high energy density.

[0037] In any embodiment, the surface density of the negative electrode film layer is 7 mg / cm 2 -14mg / cm 2 , optional 9mg / cm 2 -12mg / cm 2 .

[0038] The surface density of the negative electrode film layer is within an appropriate range, and the thickness of the negative electrode film layer is appropriate. On the one hand, the distance for the electrolyte to laterally infiltrate the electrode sheet is relatively short, and the time required for the electrolyte to completely infiltrate the negative electrode sheet is also relatively short, thereby reducing the possibility of local polarization and improving the cycle performance of the battery. On the other hand, the surface density within an appropriate range also ensures that the battery has a certain energy density.

[0039] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of a secondary battery according to one embodiment of the present application.

[0041] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0042] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0043] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0044] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0045] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0046] Description of reference numerals:

[0047] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0048] Hereinafter, the embodiments of the graphite negative electrode active material and its preparation method, the secondary battery containing the same, and the electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0054] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0055] In order to improve the process efficiency of electrode coating in the prior art, the coating speed or drying speed is usually increased. However, at high coating speed or drying speed, the micropowder in the negative electrode active material is easy to migrate to the surface of the electrode as the solvent evaporates (i.e., the micropowder floats up), which will cause the floating micropowder to block the pores on the surface of the negative electrode, affecting the wettability of the electrolyte to the negative electrode, and the liquid absorption rate of the electrode decreases. During the cycle process, some areas of the electrode cannot absorb the electrolyte in time, which may cause the active ions to be unable to be effectively embedded in the negative electrode, resulting in local polarization and uneven current distribution, resulting in black spots on the surface of the electrode and accompanied by other side reactions. The accumulation of byproducts further blocks the pores, which may cause lithium precipitation in the electrode, resulting in a decrease in the capacity retention rate of the battery and a reduction in the battery life.

[0056] [Graphite negative electrode active material]

[0057] The present application provides a graphite negative electrode active material, wherein the volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5 μm-3 μm; and the graphite negative electrode active material includes a primary particle morphology.

[0058] In some embodiments, the volume distribution particle size Dv1 of the graphite negative electrode active material can be selected as 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm or a value in the range consisting of any two of the above points.

[0059] The volume distribution particle size Dv1 of the graphite negative electrode active material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 1%.

[0060] The Dv1 of the graphite negative electrode active material can be tested by a method known in the art. For example, GB / T 19077-2016 can be referred to and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.

[0061] The graphite negative electrode active material has a large volume distribution particle size Dv1, and the graphite negative electrode active material has a relatively small content of micropowder, which can effectively reduce the phenomenon of micropowder floating during coating or drying, increase the liquid absorption rate of the negative electrode plate, and improve the wettability of the electrolyte to the negative electrode plate, so that the electrolyte can fully infiltrate the negative electrode plate during the lithium insertion and extraction process, reduce the possibility of local polarization, and make the current of the negative electrode plate during the cycle process uniformly distributed, reduce the possibility of side reactions at the negative electrode interface during the cycle process, and reduce the effect of the byproducts caused by the side reactions blocking the pores on the cycle performance of the battery. If the volume distribution particle size Dv1 of the graphite negative electrode active material is too large, the micropowder content between particles is too small, and the electrical contact between particles cannot be effectively maintained, which affects the kinetic performance of the battery, resulting in the occurrence of lithium precipitation, and further affects the cycle performance of the battery.

[0062] Herein, primary particles have a meaning known in the art. "Primary particles" are also called single particles, and generally refer to non-agglomerated particles. Primary particles can be confirmed by using a scanning electron microscope (SEM) image.

[0063] The graphite negative electrode active material contains primary particles, which have excellent structural stability, which helps to reduce the structural fragmentation of the graphite negative electrode active material caused by expansion and contraction during the cycle process, improve the structural stability of the graphite negative electrode active material, and thus improve the cycle performance of the secondary battery.

[0064] In summary, the present application can effectively improve the cycle performance of the battery and extend the service life of the battery by limiting the volume distribution particle size Dv1 of the graphite negative electrode active material and the particle type of the graphite negative electrode active material.

[0065] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g.

[0066] In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 0.4 m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.85m 2 / g, 0.85m 2 / g, 1.05m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.3m 2 / g, 1.4m 2 Any value in / g or a range consisting of any two values ​​in it.

[0067] The specific surface area of ​​the graphite negative electrode active material can be measured by instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0068] The graphite negative electrode active material has a low specific surface area, which makes the material have low surface activity, thereby reducing the consumption of active ions by the side reactions between the graphite negative electrode active material and the electrolyte, and improving the cycle performance and storage stability of the battery.

[0069] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is 0.6 m 2 / g-1.3m 2 / g.

[0070] In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 0.6 m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.85m 2 / g, 0.85m 2 / g, 1.05m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.3m 2Any value in / g or a range consisting of any two values ​​in it.

[0071] As mentioned above, graphite negative electrode active materials have a small specific surface area, which can reduce the consumption of active ions by the side reactions between graphite negative electrode active materials and electrolytes, and improve the cycle performance and storage stability of the battery. However, if the specific surface area is too small, it will affect the wettability of the electrolyte to the electrode, affect the kinetic performance of the electrode, and easily cause lithium precipitation, which will affect the cycle life and storage performance of the battery. A suitable range of specific surface area can further improve the cycle life and storage performance of the battery.

[0072] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 12 μm-16 μm.

[0073] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected as any value of 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, or a range consisting of any two values ​​thereof.

[0074] The volume distribution particle size Dv50 of the graphite negative electrode active material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured by instruments and methods known in the art. For example, the particle size distribution laser diffraction method according to GB / T 19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as the Mastersizer-3000 of Malvern for testing.

[0075] The graphite negative electrode active material has a large volume distribution particle size Dv50, which is conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, which is conducive to the full infiltration of the electrolyte into the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of black spots on the negative electrode on the cycle life and storage performance of the battery.

[0076] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 13 μm-15 μm.

[0077] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected as any value of 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, or a range consisting of any two values ​​thereof.

[0078] The graphite negative electrode active material has a suitable volume distribution particle size Dv50, which is conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, which is conducive to the electrolyte fully infiltrating the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of the black spot phenomenon on the battery cycle life and storage performance. At the same time, it is also conducive to improving the transmission performance of active ions and electrons. The plate has excellent kinetic performance and reduces the impact of lithium precipitation on the battery life and storage performance.

[0079] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of the primary particles accounts for greater than or equal to 80%.

[0080] In some embodiments, based on the total amount of the graphite negative electrode active material, the amount of primary particles in the graphite negative electrode active material accounts for 85%-100%.

[0081] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material can be selected as any value among 80%, 85%, 90%, 95%, 100% or a range consisting of any two values ​​therein.

[0082] In some embodiments, the particles in the graphite negative electrode active material include primary particles and secondary particles. In this article, secondary particles have a meaning known in the art, and "secondary particles" refer to agglomerated particles formed after agglomeration between multiple original particles or primary particles. The force for agglomeration between particles can be assisted by another substance (e.g., a sticky chemical substance) to assist agglomeration.

[0083] The number ratio of primary particles can be determined by instruments and methods known in the art. An example is as follows: lay and stick the graphite negative electrode active material on the conductive glue to make a sample to be tested with a length × width = 6 cm × 1.1 cm. Use a scanning electron microscope; an energy spectrometer (such as ZEISS SEM (sigma300)) to test the morphology of the particles in the sample to be tested. The test can refer to JY / T010-1996. In order to ensure the accuracy of the test results, multiple (for example, 10 or 20) different areas can be randomly selected from the sample to be tested for scanning testing, and at a certain magnification (for example, 500 times or 1000 times), the number of primary particles and the total number of particles in the test area are counted. The ratio of the number of primary particles to the total number of particles in any test area is the number ratio of primary particles in the area, and the average value of the test results of 10 test areas is taken as the number ratio of primary particles. In order to ensure the accuracy of the results, multiple samples to be tested (for example, 5 or 10) may be prepared to repeat the above test, and the average value of the test results of each sample to be tested is taken as the percentage of primary particles in the graphite negative electrode active material.

[0084] The primary particles within the above range help to reduce the structural fragmentation of the graphite negative electrode active material due to expansion and contraction during the cycle process, improve the structural stability of the graphite negative electrode active material, and further improve the cycle stability and storage stability of the secondary battery.

[0085] In some embodiments, the gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g.

[0086] In some embodiments, the gram capacity of the graphite negative electrode active material can be selected as any value among 340mAh / g, 341mAh / g, 342mAh / g, 343mAh / g, 344mAh / g, 345mAh / g, 346mAh / g, 347mAh / g, 349mAh / g, 350mAh / g, 351mAh / g, 352mAh / g, or a range consisting of any two values ​​therein.

[0087] The gram capacity can be measured by any known method in the art. For example, the graphite negative electrode active material sample can be mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent NMP to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode and the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells are assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0088] Graphite negative electrode active materials have high gram capacity and provide the material basis for high energy density batteries.

[0089] In some embodiments, the gram capacity of the graphite negative electrode active material is 341 mAh / g-347 mAh / g. In some embodiments, the gram capacity of the graphite negative electrode active material can be selected as any value of 341 mAh / g, 342 mAh / g, 343 mAh / g, 344 mAh / g, 345 mAh / g, 346 mAh / g, 347 mAh / g, or a range consisting of any two of them.

[0090] The gram capacity of the graphite negative electrode active material is within a suitable range, which can improve the energy density of the battery. At the same time, when the gram capacity of the graphite negative electrode active material is within the above range, its particle strength is high, which reduces the possibility of the particles tending to be flat during the cold pressing of the pole piece, avoids the electrolyte transmission path from becoming significantly longer during the cold pressing process, is beneficial to reducing the tortuosity of the negative electrode pole piece, is beneficial to the circulation of the electrolyte, improves the wetting effect of the electrolyte on the pole piece, and improves the cycle performance and storage performance of the battery.

[0091] In some embodiments, the tap density of the graphite negative electrode active material is 1.2 g / cm 3 -1.4g / cm 3 .

[0092] In some embodiments, the tap density of the graphite negative electrode active material may be 1.2 g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 Or a value within the range formed by any two of the above points.

[0093] In this article, the term "tap density" refers to the density of a powder material after vibration compression under certain conditions.

[0094] The tap density can be measured by any known method in the art. For example, GB / T5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Better BT-301. The test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0095] When the tap density of the graphite negative electrode active material is within the above range, it is conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, improving the wettability of the electrolyte to the negative electrode plate, and improving the cycle performance and storage performance of the secondary battery. At the same time, the appropriate tap density can also increase the compaction density of the negative electrode film layer, thereby improving the energy density of the secondary battery.

[0096] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is 1.20-1.70. In some embodiments, the (Dv90-Dv10) / Dv50 of the graphite negative electrode active material can be selected as any value of 1.20, 1.30, 1.40, 1.50, 1.60, 1.70 or a range consisting of any two values ​​thereof.

[0097] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is 1.35-1.60. In some embodiments, the (Dv90-Dv10) / Dv50 of the graphite negative electrode active material can be selected as any value among 1.35, 1.45, 1.55, 1.60 or a range consisting of any two values ​​therein.

[0098] The volume distribution particle sizes Dv10, Dv50, and Dv90 of the graphite negative electrode active material are well-known in the art, and respectively represent the particle sizes corresponding to when the cumulative volume distribution percentage of the material reaches 10%, 50%, and 90%, and can be tested by methods well-known in the art. As an example, GB / T 19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as the Mastersizer-3000 of Malvern.

[0099] The particle size distribution of the graphite negative electrode active material that meets the above range is helpful to improve the concentration of the particle size of the graphite negative electrode active material, improve the concentration of the particle arrangement, reduce the tortuosity of the negative electrode plate, reduce the transmission path of the electrolyte, so that the electrolyte fully infiltrates the negative electrode plate, improve the cycle performance of the battery, and at the same time reduce the uneven distribution of active ions in the graphite negative electrode active material caused by the large difference in particle size, reduce the side reaction of the graphite negative electrode active material with smaller particle size and the electrolyte, and improve the cycle performance and storage performance of the secondary battery. At the same time, the particle size distribution of the graphite negative electrode active material is within the above range, and its particle stacking performance is good, which is conducive to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0100] The present application also provides a method for preparing a graphite negative electrode active material, comprising the following steps: providing raw materials; processing the raw materials to obtain a precursor; graphitizing the precursor to obtain an intermediate product; screening the intermediate product to obtain a graphite negative electrode active material; wherein the volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5μm-3μm; and the graphite negative electrode active material includes a primary particle morphology.

[0101] By adopting the above preparation method, a graphite negative electrode active material having a volume distribution particle size Dv1 within a suitable range and containing primary particles can be prepared, which can further improve the cycle performance of the battery and extend the service life of the battery.

[0102] In some embodiments, the feedstock includes at least one of petroleum coke, needle coke, and pitch coke.

[0103] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0104] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0105] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0106] In some embodiments, the feedstock comprises petroleum coke.

[0107] Petroleum coke has excellent anisotropy, which is conducive to the preparation of low-graphitization, low-expansion graphite materials, which is conducive to the long cycle life of the battery. At the same time, petroleum coke has high compaction density and high gram capacity, which is conducive to improving the energy density of the battery. In addition, the source of petroleum coke is more extensive, which is conducive to industrial production.

[0108] The above-mentioned raw materials usually include at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fiber structures.

[0109] In some embodiments of the present application, based on the total volume of the raw material structure, the volume proportion of the mosaic and regional structures in the raw material is greater than or equal to 60%, and can be optionally 65%-80%.

[0110] In this application, the volume proportion of mosaic and regional structures in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type and regional-type structure optical tissues by the total number of statistical testing points as the volume proportion of the mosaic-type and regional-type structures in the raw material.

[0111] In some embodiments, the processing of the raw material specifically comprises the following steps:

[0112] crushing, shaping and classifying the raw materials to obtain a precursor;

[0113] During the classification process, a certain proportion of fine powder is removed.

[0114] Among them, the mass proportion of the removed fine powder is 10%-35%. Based on the total mass of the raw material, the volume distribution particle size Dv50 of the fine powder is 3μm-7μm, and the (Dv90-Dv10) / Dv50 of the fine powder is greater than 1.6.

[0115] In some embodiments, based on the total mass of the raw material, the mass percentage of the removed fine powder can be selected as any value of 10%, 15%, 20%, 25%, 30%, 35% or a range consisting of any two values ​​therein.

[0116] By controlling the mass ratio of removed fine powder within an appropriate range, the volume distribution particle size Dv1 of the graphite negative electrode active material can be controlled within an appropriate range, which can not only make the electrode have an excellent liquid absorption rate and the electrolyte can fully infiltrate the negative electrode, but also make the graphite particles have excellent electrical contact, thereby comprehensively improving the cycle performance of the battery.

[0117] In some embodiments, in the step of crushing the raw material, a crusher, such as a jaw crusher, can be used to crush the raw material. For example, the raw material can be crushed to a set particle size before screening.

[0118] In some embodiments, in the step of shaping the raw material, a shaping machine can be used to shape the crushed raw material. The shaping process can reduce burrs on the surface of the crushed raw material, which is conducive to obtaining a rounded graphite negative electrode active material and improving the compaction density of the negative electrode film layer.

[0119] In some embodiments, in the step of classifying the raw materials, an air flow classifier can be used to classify the shaped raw materials. Optionally, the induced air frequency can be greater than or equal to 20 Hz, and the classification frequency can be greater than or equal to 65 Hz. Classification can reduce the content of large particles and small particles in the precursor.

[0120] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0121] In some embodiments, the maximum power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% or any range of values ​​between the rated power of the graphitization treatment equipment. It can be understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization furnace, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and it can be selected according to the actual situation.

[0122] The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.

[0123] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000W-32000W.

[0124] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000W-30000W.

[0125] In some embodiments, the maximum power of the graphitization treatment is 23000 W-25000 W. For example, it can be 23000 W, 23500 W, 24000 W, 24500 W, 25000 W, or any range therebetween.

[0126] In some embodiments, the graphitization treatment is performed at a constant power time of 10 h to 50 h at the maximum power.

[0127] In some embodiments, the graphitization treatment is performed at a constant power time of maximum power of 10 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 42 h, 45 h, 48 h, 50 h, or any range therebetween.

[0128] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment is performed at a constant power time of maximum power for 10 hours to 30 hours.

[0129] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is performed at a constant power time of maximum power for 30 hours to 50 hours.

[0130] Appropriate graphitization treatment at the constant power time of maximum power is not likely to cause excessive rearrangement of the precursor, resulting in a high specific surface area of ​​the graphite material after graphitization and deterioration of the cycle performance; it can also effectively increase the gram capacity of the graphite material, thereby facilitating the simultaneous improvement of the energy density and cycle life of the secondary battery.

[0131] In some embodiments, the volume distribution particle size Dv50 of the precursor is 12 μm-18 μm. In some embodiments, the volume distribution particle size Dv50 of the precursor can be selected as 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or any range therebetween.

[0132] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the precursor is 1.2-1.8. In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the precursor can be selected as 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or any range therebetween.

[0133] Regulating the volume distribution particle size Dv50 or particle size distribution of the precursor within a suitable range is beneficial to the volume distribution particle size Dv50 and specific surface area of ​​the graphite negative electrode active material within a suitable range, thereby obtaining a graphite negative electrode active material with excellent cycle stability and storage stability, which is beneficial to improving the cycle life and storage performance of the battery.

[0134] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0135] In one embodiment of the present application, a secondary battery is provided.

[0136] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0137] [Negative electrode]

[0138] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a graphite negative electrode active material in any embodiment or prepared by the preparation method in any embodiment.

[0139] In some embodiments, the compaction density of the negative electrode film layer is 1.35 g / cm 3 -1.65g / cm 3 In some embodiments, the compaction density of the negative electrode film layer may be 1.35 g / cm 3 , 1.40g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 Or any range of values ​​in between.

[0140] In the present application, the compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode plate test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode plate. Then wipe off the weighed electrode film layer, weigh the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0141] The negative electrode film layer has a high compaction density, which can improve the energy density of the battery. However, the high compaction density will lead to small pores in the negative electrode plate, and the graphite powder will block the pores, affecting the wettability of the electrolyte to the plate. The present application can effectively compensate for the effect of high compaction density on the wettability of the plate by controlling the volume distribution particle size Dv1 of the graphite negative electrode active material, improve the wettability of the plate and increase the cycle life of the battery under the premise that the battery has a high energy density.

[0142] In some embodiments, the compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.55g / cm3 In some embodiments, the compaction density of the negative electrode film layer may be 1.40 g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 , 1.55g / cm 3 Or any range of values ​​in between.

[0143] The compaction density of the negative electrode film layer is within an appropriate range, so that the negative electrode film layer has an appropriate number of pores, the electrolyte has good wettability to the negative electrode plate, the possibility of local polarization is reduced, and the cycle performance and storage performance of the battery are improved. On the other hand, the compaction density within an appropriate range also ensures that the battery has a certain energy density.

[0144] In some embodiments, the surface density of the negative electrode film layer is 7 mg / cm 2 -14mg / cm 2 In some embodiments, the surface density of the negative electrode film layer can be 7 mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 Or any range of values ​​in between.

[0145] In some embodiments, the surface density of the negative electrode film layer is 9 mg / cm 2 -12mg / cm 2 In some embodiments, the surface density of the negative electrode film layer can be 9 mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 Or any range of values ​​in between.

[0146] The surface density of the negative electrode film layer can be tested using any method and equipment known in the art. As an example, take the cold-pressed negative electrode sheet, punch it into a small disc with an area of ​​S1, weigh it, and record it as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. The surface density of the negative electrode film layer = (weight of the negative electrode sheet M1-weight of the negative electrode collector M0) / S1.

[0147] The surface density of the negative electrode film layer is within an appropriate range, and the thickness of the negative electrode plate is appropriate. On the one hand, the distance for the electrolyte to laterally infiltrate the plate is relatively short, the tortuosity of the plate is small, and the time required for the electrolyte to completely infiltrate the negative electrode plate is also relatively short, thereby reducing the possibility of local polarization and improving the cycle performance of the battery. On the other hand, the surface density within an appropriate range also ensures that the battery has a certain energy density.

[0148] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0149] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0150] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite negative electrode active material. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0151] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0152] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0153] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0154] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as graphite negative electrode active material, conductive agent, binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0155] [Positive electrode]

[0156] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0157] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0158] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0159] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0160] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0161] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0162] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0163] [Electrolytes]

[0164] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0165] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0166] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0167] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0168] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0169] [Isolation film]

[0170] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0171] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0172] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0173] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0174] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0175] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0176] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0177] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0178] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0179] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0180] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0181] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0182] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0183] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0184] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0185] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0186] Example

[0187] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0188] 1. Preparation method

[0189] Example 1

[0190] (1) Preparation of graphite negative electrode active materials

[0191] The petroleum coke raw material with a volume proportion of 60% of the mosaic and regional structures is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped and graded, and a certain amount of fine powder is removed during the grading process to obtain a precursor, wherein the mass of the removed fine powder accounts for 21% of the total mass of the petroleum coke raw material, and the volume distribution particle size Dv50 of the precursor is 15.5μm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.50, wherein the fine powder refers to particles with a Dv50 particle size of 3-7μm and a particle size distribution (Dv90-Dv10) / Dv50 greater than 1.6;

[0192] The precursor is graphitized in an Acheson furnace at a graphitization temperature of 2800° C. The maximum power used in the graphitization is 24000W (herein, it refers to the actual power used by the Acheson furnace, which accounts for about 85% of the rated power of the Acheson furnace). After the power is kept constant for 40 hours, the surface temperature of the graphite crucible of the Acheson furnace is cooled to 300° C. to obtain an intermediate product.

[0193] The intermediate product is screened and demagnetized to obtain graphite negative electrode active material. The graphite negative electrode active material is mainly composed of primary particles, which account for more than 85% of the material. The graphite negative electrode active material has Dv1 = 2.0μm, Dv50 = 14.3μm, and BET = 1.1m 2 / g.

[0194] (2) Preparation of negative electrode sheet

[0195] The graphite negative electrode active material prepared above, the conductive agent Super P, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber SBR were mixed at a dry material mass ratio of 95.4:1.6:1.2:1.8, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The compacted density of the negative electrode film layer is 1.40 g / cm 3 , surface density is 9.6mg / cm 2 .

[0196] (2) Preparation of positive electrode sheet

[0197] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compacted density of the positive electrode sheet is 2.50g / cm 3 , surface density is 19.7mg / cm 2 .

[0198] 4) Preparation of electrolyte

[0199] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.

[0200] 5) Isolation film

[0201] Polypropylene film is used as the isolation film.

[0202] 6) Preparation of secondary batteries

[0203] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0204] The preparation method of Example 2-3 is basically the same as that of Example 1, except that the mass percentage of the removed fine powder is different, as shown in Table 1.

[0205] Table 1

[0206] Preparation parameters Serial number Proportion of fine powder removed Example 1 21% Example 2 15% Example 3 31% Comparative Example 1 7% Comparative Example 2 39%

[0207] The preparation methods of Examples 4-6 are basically the same as those of Example 1, except that the volume distribution particle size Dv50 of the precursor, the particle size distribution (Dv90-Dv10) / Dv50 of the precursor and the constant power time of the graphitization treatment at maximum power are regulated, as shown in Table 2.

[0208] Table 2

[0209]

[0210] The preparation method of Comparative Example 1-2 is basically the same as that of Example 1, except that the mass percentage of the removed fine powder is as shown in Table 1.

[0211] The preparation method of the graphite negative electrode active material in Comparative Example 3 is as follows:

[0212] S1: crushing the needle-shaped raw coke, shaping it, grading it, removing fine powder, and obtaining a precursor with a Dv50 of 11 μm;

[0213] S2: Add the precursor obtained in step S1 to the reactor, and add 10% of the mass of the precursor asphalt (Dv50 of the asphalt is 5μm-8μm) for granulation, heat to 560°C at a rate of 10°C / min at room temperature, and then keep the temperature constant for 8 hours to obtain intermediate 1, and the Dv50 of intermediate 1 is 18μm;

[0214] S3: Add the intermediate 1 obtained in step S2 into a graphitization furnace, heat it to 3000°C for graphitization treatment, the power of the graphitization treatment adopts the rated power of the equipment 29000W, and screen and demagnetize the obtained intermediate product to obtain a graphite negative electrode active material; the graphite negative electrode active material is mainly in the form of secondary particles, the content of the secondary particle morphology is about 70% or more, Dv1 is 2.3μm, Dv50 is 14μm, and the gram capacity is 357mAh / g.

[0215] 2. Performance Test

[0216] 1. Secondary battery black spot test

[0217] At 25° C., the batteries of the above embodiments and comparative examples were charged at a constant current of 0.33C to a voltage of 3.65V, and then disassembled in a drying room to observe whether there were black spots on the surface of the negative electrode plate;

[0218] (1) The total area of ​​black spots / total area of ​​the negative electrode is ≤1%, and the area of ​​black spots in a single electrode is ≤8% of the area of ​​a single electrode.

[0219] (2) 1% < total area of ​​black spots / total area of ​​negative electrode ≤ 3%, or 8% < area of ​​black spots in a single electrode / area of ​​a single electrode ≤ 15% is defined as secondary black spots;

[0220] (3) The total area of ​​black spots / total area of ​​the negative electrode is greater than 3%, or the area of ​​black spots in a single electrode / area of ​​a single electrode is greater than 15%, which is defined as level 3 black spots.

[0221] 2. Cycle performance test of secondary batteries

[0222] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0223] 3. Storage performance test of secondary batteries

[0224] In an environment of 25°C, the charge and discharge test was carried out, charging at a constant current of 1C to a voltage of 3.65V, then charging at a constant voltage of 3.65V to a current ≤0.05C, and then discharging the battery at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge process, and the discharge capacity of the first cycle is recorded, which is the initial discharge capacity, recorded as C0. Then the fully charged battery cell is placed in an environment of 60°C for different periods of time, and the remaining capacity C1 is tested at 25°C every 30 days. This is a storage cycle, and the discharge capacity this time is the discharge capacity after the first storage. Subsequently, the first storage test process is repeated, the discharge capacity value during the storage process is recorded, and the 120-day cycle capacity retention rate is recorded.

[0225] 3. Results

[0226] As can be seen from Table 3, the volume distribution particle size Dv1 of the graphite negative electrode active material provided in Examples 1-3 of the present application is 1.5-3 μm; and the graphite negative electrode active material is mainly in the form of primary particles. From the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the graphite negative electrode active material of the present application can reduce the possibility of black spots on the pole piece, increase the number of cycles of the battery, improve the cycle life of the battery, and extend the service life.

[0227] Table 3

[0228]

[0229] As can be seen from Table 4, the volume distribution particle size Dv50 of the graphite negative electrode active material is 12μm-16μm, which can effectively take into account the cycle life and storage stability of the battery. The volume distribution particle size Dv50 of the graphite negative electrode active material is 13μm-15μm, which can further improve the cycle life and storage stability of the battery.

[0230] As can be seen from Table 4, the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, which can effectively balance the cycle life and storage stability of the battery. The specific surface area of ​​the graphite negative electrode active material is 0.6m 2 / g-1.3m 2 / g, which can further improve the cycle life and storage stability of the battery.

[0231] Table 4

[0232]

[0233] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphite negative electrode active material, characterized in that: The volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5 μm-3 μm; the graphite negative electrode active material includes a primary particle morphology.

2. The graphite negative electrode active material according to claim 1, characterized in that: The specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, optional 0.6m 2 / g-1.3m 2 / g.

3. The graphite negative electrode active material according to claim 1 or 2, characterized in that: The volume distribution particle size Dv50 of the graphite negative electrode active material is 12 μm-16 μm, and can be optionally 13 μm-15 μm.

4. The graphite negative electrode active material according to any one of claims 1 to 3, characterized in that Based on the total number of particles of the negative graphite negative electrode active material, the number of the primary particles accounts for greater than or equal to 80%, and can be optionally 85%-100%.

5. The graphite negative electrode active material according to any one of claims 1 to 4, characterized in that The gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g, and can be optionally 341 mAh / g-347 mAh / g.

6. The graphite negative electrode active material according to any one of claims 1 to 5, characterized in that The tap density of the graphite negative electrode active material is 1.2 g / cm 3 -1.4g / cm 3 .

7. The graphite negative electrode active material according to any one of claims 1 to 6, characterized in that The particle size distribution of the graphite negative electrode active material is (Dv90-Dv10) / Dv50 is 1.20-1.70, and can be optionally 1.35-1.

60.

8. A method for preparing a graphite negative electrode active material, characterized in that: The steps include: Provide raw materials; Processing the raw material to obtain a precursor; The precursor is graphitized to obtain an intermediate product; The intermediate product is subjected to screening treatment to obtain a graphite negative electrode active material; The volume distribution particle size Dv1 of the graphite negative electrode active material is 1.5 μm-3 μm; and the graphite negative electrode active material includes a primary particle morphology.

9. The preparation method according to claim 8, characterized in that: The processing of raw materials specifically comprises the following steps: crushing, shaping and classifying the raw materials to obtain a precursor; During the classification process, a certain proportion of fine powder is removed. Among them, the mass proportion of the removed fine powder is 10%-35%, based on the total mass of the raw material; the volume distribution particle size Dv50 of the fine powder is 3μm-7μm, and the (Dv90-Dv10) / Dv50 of the fine powder is greater than 1.

6.

10. The preparation method according to claim 8 or 9, characterized in that: The maximum power of the graphitization treatment is 70%-90% of the rated power of the graphitization equipment.

11. The preparation method according to claim 10, characterized in that: The maximum power of the graphitization treatment is 23000W-25000W; and / or the constant power time of the graphitization treatment at the maximum power is 10h-50h.

12. The preparation method according to any one of claims 8 to 11, characterized in that The precursor satisfies at least one of the following conditions: The volume distribution particle size Dv50 of the precursor is 12 μm-18 μm; and / or, The particle size distribution of the precursor (Dv90-Dv10) / Dv50 is 1.2-1.

8.

13. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode sheet comprises the graphite negative electrode active material according to any one of claims 1 to 7 or the graphite negative electrode active material prepared by the preparation method according to any one of claims 8 to 12.

14. The secondary battery according to claim 13, characterized in that: The compaction density of the negative electrode film layer is 1.35 g / cm 3 -1.65g / cm 3 , optional 1.40g / cm 3 -1.55g / cm 3 .

15. The secondary battery according to claim 13 or 14, characterized in that: The surface density of the negative electrode film layer is 7 mg / cm 2 -14mg / cm 2 , optional 9mg / cm 2 -12mg / cm 2 .

16. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 13 to 15.

Citation Information

Patent Citations

  • Secondary battery, device, artificial graphite, and preparation method

    CN113207313A

  • Artificial graphite and preparation method thereof, and secondary battery and electric device containing artificial graphite

    CN116745956A

  • Method of producing non-aqueous electrolyte secondary battery, and negative electrode active material

    EP4057383A2

  • Negative electrode active material and method for preparation thereof, secondary battery, and apparatus including secondary battery

    US20220166009A1

  • Negative electrode active material and preparation method therefor, secondary battery, and device including secondary battery

    WO2021217620A1

Cited By

  • Graphite negative electrode active material and preparation method therefor, secondary battery containing same, and electric device

    EP4800776A1